2019
DOI: 10.1002/er.4969
|View full text |Cite
|
Sign up to set email alerts
|

Optimal roof structure with multilayer cooling function materials for building energy saving

Abstract: Summary Both cool roof and phase change thermal storage are promising technologies in decreasing building energy consumption. Combining these two technologies is likely to further enhance the thermal comfort of the building as well as reduce air condition loads. In this paper, the cooling performance and energy‐saving effects of four types of roof (normal roof, phase change material [PCM] roof, cool roof, and cool PCM roof [cool roof coupled with PCM]) were investigated under a simulated sunlight. Experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Arıcı et al [59] found that PCM temperature varied between 6 °C to 34 °C and a PCM layer thickness varied between 1-20 mm can improve the building thermal performance and time lag by 10.3 h in three different Turkish cities. Zhang et al [60] indicated that PCMs of melting temperature varied between 22 °C-28 °C, placed to the interior position with 5mm thickness could reduce the indoor building surface temperature and the heat transfer by 6.6 °C and 52.9% under China weather conditions. All in all, these parameters need to be studied in parallel to obtain the best thermal performance of PCMs [61].…”
Section: Phase Change Materialsmentioning
confidence: 99%
“…Arıcı et al [59] found that PCM temperature varied between 6 °C to 34 °C and a PCM layer thickness varied between 1-20 mm can improve the building thermal performance and time lag by 10.3 h in three different Turkish cities. Zhang et al [60] indicated that PCMs of melting temperature varied between 22 °C-28 °C, placed to the interior position with 5mm thickness could reduce the indoor building surface temperature and the heat transfer by 6.6 °C and 52.9% under China weather conditions. All in all, these parameters need to be studied in parallel to obtain the best thermal performance of PCMs [61].…”
Section: Phase Change Materialsmentioning
confidence: 99%
“…It has been found that the heat storage capacity of PCMs increases with their quantity, allowing for greater energy savings. However, this concept has its limitations; for instance, Zhang et al [5] found that adding a 5 mm layer of PCM to the roof only lowered the highest indoor temperature by 2 • C. Additionally, increasing the thickness from 5 mm to 10 mm lowered the highest indoor temperature by only 0.5 • C, and by 0.3 • C when the thickness was further increased to 15 mm. Therefore, the viability of the technology depends not only on the quantity of PCM but also on its substantial impact on the associated costs [6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, several researchers have studied the incorporation of PCM in building applications, such as wallboard building, [40][41][42] building envelope, [43][44][45][46][47] wall coatings, 48 concrete materials, 49-51 bricks, [52][53][54] and building roof for reducing the energy requirements. 55 In the present work, rigid polyurethane composites sandwiched between tin panels are prepared by integrating MF/LA-PA microcapsules into polyurethane foam. Melamine formaldehyde shells are chemically and mechanically stable, have a long shelf life, are compatible with a wide range of polymeric matrixes, and maintain inertness towards PCM material.…”
Section: Introductionmentioning
confidence: 99%
“…The main benefit of integrating PCM thermal energy storage units with building technologies includes both their high storage capacities at a short temperature span and increased energy efficiency in new and refurbished buildings in combination with other active systems. Therefore, several researchers have studied the incorporation of PCM in building applications, such as wallboard building, 40‐42 building envelope, 43‐47 wall coatings, 48 concrete materials, 49‐51 bricks, 52‐54 and building roof for reducing the energy requirements 55 …”
Section: Introductionmentioning
confidence: 99%